2005
DOI: 10.1143/jpsj.74.1431
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solutions with Jacobi Elliptic Functions of Two Nonlinear Models for Ion-Acoustic Plasma Waves

Abstract: The periodic wave solutions of two nonlinear models for ion-acoustic plasma waves, including the mixed Korteweg-de Vries (KdV) and modified KdV equation and the (3 þ 1)-dimensional modified Zakharov-Kuznetsov equation, are obtained by using the F-expansion method and introducing appropriate transformations. In the limiting cases, the solitary wave solutions of the equations are also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…It is concluded from these tables that the presented results are more accurate than the results given in [6,36,37]. The approximate solutions ( ) and ( ) of problem (31) From these figures, there is agreement between the approximate and exact solutions.…”
Section: Examplesupporting
confidence: 51%
See 4 more Smart Citations
“…It is concluded from these tables that the presented results are more accurate than the results given in [6,36,37]. The approximate solutions ( ) and ( ) of problem (31) From these figures, there is agreement between the approximate and exact solutions.…”
Section: Examplesupporting
confidence: 51%
“…It is concluded that the proposed method with all choices of θ and is more accurate than the methods given in [6,36,37]. Consider the following two examples.…”
Section: Numerical Resultsmentioning
confidence: 92%
See 3 more Smart Citations